Increased diversity of a cervical microbiome associates with cervical cancer - Zeber-Lubecka, Natalia; Kulecka, Maria; Lindner, Bogusław; Krynicki, Ryszard; Paziewska, Agnieszka; Nowakowski, Andrzej; Bidzinski, Mariusz; Ostrowski, Jerzy (Frontiers in Oncology, 2022)
The cervical microbiome (CM) is a complex ecosystem that can change in response to gynecological cancers. We aimed to evaluate changes in the CM of patients who underwent chemoradiation (CRT) therapy for locally advanced cervical cancer. Before and after CRT, cervical swab samples were collected from 16 patients with squamous cell carcinoma of the cervix, and 30 healthy women. All samples were subjected to 16s rRNA-Seq analysis. In healthy premenopausal women the CM comprised mostly Lactobacillus (>90%); the CM community in samples from both pre- and postmenopausal pre-treatment cancer patients was heterogeneous, with a low proportion of Lactobacillus in younger cases. On the genus level, 27 and 11 taxa differentiated healthy controls from cancer patients in pre- and postmenopausal age groups, while 31 and 2 genera differentiated pre- and post-radiation samples and pre-radiation and the follow-up samples, respectively. Microbiome diversity was significantly higher in pre-treatment patients than in healthy controls. The results reveal significant alterations in the CM of cervical cancer patients relative to that in healthy controls; these changes were more striking after CRT. However, further research is needed to determine whether alteration of the CM offers new therapeutic options.